2019
DOI: 10.1055/s-0039-1692469
|View full text |Cite
|
Sign up to set email alerts
|

Stress Radiography for the Diagnosis of Medial Glenohumeral Ligament Rupture in Canine Shoulders

Abstract: Objectives This study aimed to describe a stress radiography to detect medial glenohumeral ligament rupture and to investigate the repeatability and reproducibility of this test. Materials and Methods Six adult Beagle cadavers were used. Both shoulders of each dog were randomly assigned into two groups: a normal shoulder group (NS group) and an affected shoulder group (AS group) where the medial glenohumeral ligament was arthroscopically transected. Goniometry, image analysis and radiography (norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…In addition, since there were only 13 dogs with infraspinatus-fluid, the results might reflect a type-II error. Based on the lack of evidence that increased SAA was related to injury we agree with others 11,15,39,40 and question the previously suggested clinical relevance of SAA. [7][8][9] The structures evaluated in our study are those typically examined as part of a standard shoulder ultrasonography.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, since there were only 13 dogs with infraspinatus-fluid, the results might reflect a type-II error. Based on the lack of evidence that increased SAA was related to injury we agree with others 11,15,39,40 and question the previously suggested clinical relevance of SAA. [7][8][9] The structures evaluated in our study are those typically examined as part of a standard shoulder ultrasonography.…”
Section: Discussionsupporting
confidence: 77%
“…Measurement of shoulder abduction angles (SAA) is recommended to diagnose medial shoulder instability. [7][8][9][10] This should be followed by imaging, 6,7,[11][12][13][14][15][16] with classical 7,11,13,16 or needle arthroscopy 17 considered the gold standard to assess some intra-articular structures. However, arthroscopy cannot provide information on other periarticular shoulder muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder instability is a cause of forelimb lameness in the dog, 1,3–5 with medial shoulder instability (MSI) composing a large proportion of those cases 6–9 . The anatomy and passive and active stabilizers of the canine shoulder have been well described and it has been determined that the major passive stabilizers are the medial glenohumeral ligament (MGHL) and the tendon of the subscapularis muscle, with the MGHL playing the largest role 1,2,4,6 . Tears in these structures lead to acute or chronic instability, luxation or subluxation, pain, lameness, inflammation, and damage to the cartilage surfaces in the long term 1,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…infraspinatus, and teres minor muscles (the muscles of the rotator cuff) stabilize the shoulder when smaller magnitude displacements are applied, and the passive stabilizers, such as collateral ligaments and joint capsule, protect against larger magnitude displacements of the joint. 1,2 Shoulder instability is a cause of forelimb lameness in the dog, 1,[3][4][5] with medial shoulder instability (MSI) composing a large proportion of those cases. [6][7][8][9] The anatomy and passive and active stabilizers of the canine shoulder have been well described and it has been determined that the major passive stabilizers are the medial glenohumeral ligament (MGHL) and the tendon of the subscapularis muscle, with the MGHL playing the largest role.…”
mentioning
confidence: 99%
“…1 A recent study showed that a specific stress radiographic view can provide objective data to contribute to the diagnosis of medial shoulder joint instability. 9 In human medicine, high-field magnetic resonance arthrography (MRA) is the technique of choice to diagnose shoulder joint instability. 10,11 Benefits to MRA have also been demonstrated in veterinary medicine, 7,[12][13][14][15][16][17][18] however this technique may not be widely available, could be cost prohibitive for some owners, and requires prolonged anesthesia.…”
Section: Introductionmentioning
confidence: 99%